Synthesis of Sustainable Fuels and Intermediates from Ethanol and Methanol. Issue 10 (22nd August 2022) - Peters, Martin; Menne, Andreas; Gielisch, Hendrik
Abstract: Higher alcohols represent a highly interesting group of substances for fuels or as intermediates for the production of chemicals. Current production pathways for higher alcohols are based on fossil resources. Sustainable and largely available alcohols are methanol based on CO2 or ethanol based on biomass. ethanol and methanol can be used to produce higher alcohols in a heterogeneous catalytic process employing a Guerbet reaction. The resulting mixture consists of mainly branched and linear alcohols with a chain length distribution ranging from three to eight carbon atoms. The mixture displays very advantageous properties as fuel blend and feedstock for further processes to produce jet fuel or synthetic naphtha. Abstract : Sustainable higher alcohols and methanol can be used to synthesize value‐added intermediates and blend components for fuels. The catalytic condensation of ethanol and methanol leads to mixture of linear and branched molecules with broad chain length distribution from C3 up to C10. The reaction products are highly interesting intermediates for further fuel processing.